Answered

Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

-2(x+1)-3=-9 Yup I need help...

Sagot :

luana
[tex] -2(x+1)-3=-9\ \ \ \ \ |omiting\ the\ bracket\\\\ -2x-2-3=-9\\\\ -2x-5=-9\ \ \ \ |add\ 5\ to\ each\ side\\\\ -2x=-9+5\\\\ -2x=-4\ \ \ \ |divide\ by\ -2\\\\ x=2\\\\Solution\ is\ x=2.[/tex]
[tex]-2(x+1)-3=-9 \\\\ -2x-2-3=-9 \\\\ -2x-5=-9 \\\\ -2x=-9+5 \\\\ -2x=-4 \\\\ \boxed{x=\frac{-4}{-2}=2}[/tex]